DINAMIKA PENGEMBANGAN USAHA KOPERASI: Studi Pada Koperasi Kerajinan Keparakan Mandiri Sejahtera/ KOKKMAS Di Kampung Kerajinan Keparakan Kidul, Yogyakarta - , FEBRIANI DWI N ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The cooperative is an organization that were law and give welfare for all members. Establihment of a cooperative is inseparable from the goals of motivations and represents many people on it, so also KOKKMAS (Koperasi Kerajinan Keparakan Mandiri Sejahtera). KOKKMAS was formed to give craftsmenâs welfare in Keparakan Kidul with many programs being run. Basicly, KOKKMAS is open to all craftsmen in keparakan Kidul. KOKKMAS stand in 2010 and attended with the vision of the use to give benefits for all members. The existence of KOKKMAS does make all members excited because they offered ranging for credit and equipments. But it turns out that not all craftsmen interested to participate and enthusiasm members also didn ' t last long that some members decided to step outside. With that background the author want to know the not participate and the discharge of a craftsman in KOKKMAS and analyze of the aspect of theoretical actor. A method of research that used is a method of research qualitative approach eksplanatoris with case study. A subject of study is the craftsmen in Keparakan Kidul who does not partake in KOKKMAS. Researcher used a method of qualitative with adoption of an informer in purposive for determining criteria informer by the use of certain characteristics that can be giving information required. Criteria informer in this research is the craftsmen don ' t participate in cooperative and the craftsmen who never participate in cooperative but out of membership and still as many as craftsmen though out. The researcher used the theory of action to analyze what the reason craftsmen not participate and outside from cooperative. The theory of the action of belonging to peter hedstorm this is the theory , DBO which is the theory that stresses the reason behind every individual in performing an action covering reason ( desires ), belief or credence (belief) and a menu of alternative (opportunities).In a certain condition DBO of individuals are also affected by DBO the other actors (dyadic interaction). The result of this research showing reason not participate in a craftsmen and the discharge of a craftsmen in cooperative. The handicraftsman who not partake in cooperative caused by a craftsmen having the age of business longer than KOKKMAS, they having consumers remains